Economic Activity and Credit Market Linkages: New Evidence From Italy. (12th June 2017) - Chiorazzo, Vincenzo; D'Apice, Vincenzo; Morelli, Pierluigi; Puopolo, Giovanni Walter
Abstract : We investigate the interactions between the real economy and credit markets in Italy, focusing in particular on how the business cycle influences the risks of the banks' loan portfolio (i.e. the real effect), and in turn how the credit market affects the real economy (i.e. the credit supply effect). We find evidence of both effects, with the former conveyed primarily by the creditworthiness of large firms. Moreover, we disentangle credit supply shocks due to factors inside the banking sector (the bank lending channel) from those outside the banking sector (the borrower's balance‐sheet channel), and find that both channels have a negative and significant effect on gdp growth.